A Novel Intermetallic Nickel Aluminide (Ni3Al) as an Alternative Automotive Body Material - Ganesh Kumar, K.; Sivarao, Subramonian; T. Joseph, Sahaya Anand (IJENS Publishers, 2011)
Investigation on Intermetallic Nickel Aluminides (Ni3Al) was carried to determine the suitability of this material to replace the existing automotive body. The purpose is to produce vehicles which are lighter, more fuel efficient and cause less pollution. One key technical design strategy for improving vehicles efficiency is the light weighting. Attractive properties of Ni3Al including low density (~ 6g/cm3) resulting lightweight, high oxidation and corrosion resistance, combined with their ability to retain strength and stiffness at elevated temperatures lead to its selection as a candidate alternative material. The prime focus will be on to obtain the mechanical properties such as hardness which was tested using Vickers Micro hardness Tester. XRD was used to determine the crystal structure of the designed alloy. Microstructural properties of these alloys were examined using optical microscopy and Scanning Electron Microscopy (SEM). SEM equipped with EDX used to do compositional analysis. Heat treatment (annealing) and Tafel extrapolation tests were carried out for thermal and corrosion properties of the intermetallic nickel aluminides respectively.